Benign coccygeal dimple or dermal sinus tract: a big difference - Verjans, Marcelien; Jansen, Katrien; Van Calenbergh, Frank; De Vloo, Philippe; Proesmans, Marijke (Belgian Journal of Paediatrics, 2023)
Dermal sinus tracts are a type of closed spinal dysraphism occurring with an estimated incidence of 1/2500. They are often misdiagnosed as a benign coccygeal dimple, thereby increasing the risk of meningitis and tethering of the spinal cord. This case report describes a 3-month old infant with bacterial meningitis due to a dermal sinus tract in the lumbosacral region. After appropriate treatment with antibiotics she underwent surgical excision of the tract with intradural exploration and untethering of the cord.